2021
DOI: 10.1002/ppp3.10229
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure and diversity of oak populations in British parklands

Abstract: The largest populations of veteran oak trees in Europe are found in British parklands: managed wood pastures up to 1000 years old. Here, we present genomic evidence that parkland oak populations harbour considerable diversity and grew from local seed sources. We found some evidence for natural regeneration of offspring and for hybridization between pedunculate and sessile oak. We detected signatures of past gene flow between these two species and few regions of high differentiation within their genomes. Future… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…This study makes use of data initially collected for an investigation of oak tree genomes in relation to Acute Oak Decline and a wider population study of oak trees at four sites where research and monitoring of AOD was already taking place [41]. These sites are Attingham Park in Shropshire, Langdale Wood in Herefordshire, Hatchlands Park in Surrey and Sheen Wood in Richmond Park, Greater London.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study makes use of data initially collected for an investigation of oak tree genomes in relation to Acute Oak Decline and a wider population study of oak trees at four sites where research and monitoring of AOD was already taking place [41]. These sites are Attingham Park in Shropshire, Langdale Wood in Herefordshire, Hatchlands Park in Surrey and Sheen Wood in Richmond Park, Greater London.…”
Section: Methodsmentioning
confidence: 99%
“…Of the successfully sequenced individual trees, 351 were Q. robur, 10 were Q. petraea and 16 were hybrids, according to genome-based analyses. A further 45 trees not included in Nocchi et al 2021 [41] were identified by morphology, 43 as Q. robur, and one as Q. petraea, making a total of 394 Q. robur, 11 Q. petraea, and 16 hybrids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, temperature‐induced fluctuating selection resulting in allele frequencies changes in some genomic subregions have been observed in three successive oak generations covering the transition from the last Little Ice Age to the modern era (Saleh et al, 2022). Present‐day populations have been intensively studied and show a clear population structure as well as examples of recent secondary contacts and adaptive introgression between species (Alberto et al, 2010; Degen et al, 2021; Lepais et al, 2009; Leroy, Louvet, et al, 2020; Nocchi et al, 2022). Genome‐wide population data suggests that secondary contacts took place in the course of the current interglacial period and that they are associated with environmental changes such as temperature and precipitation shifts, since Q. robur is more adapted to cooler and wetter climate whereas Q. petraea prefers a warmer climate and well‐drained soils (Leroy et al, 2017; Leroy, Rougemont, et al, 2020; Roloff et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The goals of our study were thus two-fold: i) to contribute to a mechanistic understanding of pest resistance in Thlaspi arvense, and, more generally, ii) to explore whether non-target reads from plant sequencing can be used as proxies for studying plant biotic interactions. Considering that we are moving towards an increasingly sequencing-prone world, where more and larger datasets are being generated for many species (37)(38)(39)(40)(41)(42)(43), the use of non-target reads will likely have very broad potential.…”
Section: Introductionmentioning
confidence: 99%